Advanced Diabetic Neuropathy: A Point of no Return? - Boucek, Petr (The review of diabetic studies, 2006)
Diabetic peripheral neuropathy is the most common complication of long-standing diabetes mellitus which frequently results in clinically significant morbidities e.g. pain, foot ulcers and amputations. During its natural course it progresses from initial functional changes to late, poorly reversible, structural changes. Various interconnected pathogenetic concepts of diabetic neuropathy have been proposed based on metabolic and vascular factors, mostly derived from long-term hyperglycemia. These pathogenetic mechanisms have been targeted in several experimental and clinical trials. This review summarizes available, mainly morphological data from interventions designed to halt the progression or achieve the reversal of established diabetic neuropathy, which include the recovery of normoglycemia by pancreas or islet transplantation, polyol pathway blockade by aldose reductase inhibitors, mitigation of oxidative stress by the use of antioxidants or correction of abnormalities in essential fatty acid metabolism. Unfortunately, to date, no treatment based on pathogenic considerations has shown clear positive effects and thus early institution of optimal glycemic control remains the only available measure with proven efficacy in preventing or halting progression of diabetic neuropathy. Further experimental and clinical research employing objective reproducible parameters is clearly needed. Novel non-invasive or minimally invasive methods e.g. corneal confocal microscopy or epidermal nerve fiber counts may represent potentially useful instruments for the objective assessment of nerve damage and monitoring of treatment effects.